Refined Turbulence Modeling for Swirl Velocity in Turbomachinery Seals. (2003) - Kim, Namhyo; Rhode, David L.
Abstract : A generalized new form of the rotation-sensitive source term coefficient previously proposed by Bardina and colleagues as an extension of the standardk -ε turbulence model was developed. The proposal made by Bardina and colleagues focused on rotating flows without significant turbulence generation, and the result was a negative-valued constant coefficient. The new functional form developed here for the coefficient has global as well as local dependence. The new model predictions of laser Doppler anemometry measurements of swirling flows in labyrinth seals were compared with the swirl distribution measurements and with the standardk -ε model (i.e., no rotation source term) predictions. It was found that for the labyrinth seal cases for which detailed measurements are available, the standardk -ε model gives unsatisfactory predictions, whereas the new model gives significantly improved predictions.